2023
DOI: 10.3847/1538-4357/acc187
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Ion Temperatures at the Polar Coronal Hole Boundary

Abstract: The temperatures of the heavy ions (T i ) in the solar corona provide critical information about the heating mechanism of the million-degree corona. However, the measurement of T i is usually challenging due to the nonthermal motion, instrumental limitations, and optically thin nature of the coronal emissions. We present the measurement of T i … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…In this study, the excessive heating to Z/A ions, such as Fe VIII, Fe X, and Fe XI, was also found in the EIS observation of the polar CH. Previous studies reported T eff = 4-6 MK for Fe X at the base of a polar CH during the solar minimum (Hahn et al 2010;Zhu et al 2023), which is consistent with 3PAMIS and EIS observations during the 2017 TSE.…”
Section: Preferential Heatingsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the excessive heating to Z/A ions, such as Fe VIII, Fe X, and Fe XI, was also found in the EIS observation of the polar CH. Previous studies reported T eff = 4-6 MK for Fe X at the base of a polar CH during the solar minimum (Hahn et al 2010;Zhu et al 2023), which is consistent with 3PAMIS and EIS observations during the 2017 TSE.…”
Section: Preferential Heatingsupporting
confidence: 89%
“…This effect might be evident in open-field structures where fast outflows in the lower corona are expected. Consequently, different Doppler shifts along the LOS may broaden profiles in open-field structures (e.g., Akinari 2007;Zhu et al 2023).…”
Section: Los Integrationmentioning
confidence: 99%
“…Thus, with the current data sets, we were able to obtain density estimates but not temperature. Therefore, we used the reported temperature values, e.g., T log 6.20 10 = ( ) in the quiet Sun obtained by Doschek & Warren (2019), and for the coronal hole case, we used the temperature values ( T K log 5.9 6.2 10 » ( ) -) presented by Zhu et al (2023). They are derived from different intensity ratios observed by Hinode/EIS.…”
mentioning
confidence: 99%